Anomalous dielectric response in the triple perovskite ruthenate Ba3BiRu2O9. (16th November 2022) - Kumar, Jitender; Dey, Kaustav; Panja, Soumendra Nath; Nair, Sunil
Abstract: We have investigated the magnetic, dielectric and thermal properties of the S R u = 1 magnetic dimer Ba3 BiRu2 O9, which is known to exhibit a spin-gap opening in conjunction with a first-order magneto-elastic phase transition at ∼175 K. Above the spin-gap temperature, the temperature dependence dielectric constant shows a peak like feature with pronounced frequency dependence. The critical slowing down behavior of this frequency dispersion suggests that a ferroelectric relaxor like electrical glassy state exists above the spin-gap opening temperature regime. The extermination of frequency dispersion—right at the magneto-elastic phase transition, is suggestive of a strong coupling between the lattice and charge-spin degrees of freedom in this triple perovskite system.